Konsep Pendidikan Inklusif Pada Lembaga Pendidikan Anak Usia Dini - Heldanita, Heldanita (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2016)
Inclusive education should be started since early childhood. Education is a basic need of every human being, as well as early childhood education that develop the whole potential of the whole child. In addition to laws and regulations that support the implementation of early childhood education, conceptual and scientific studies of child development, have shown their positive values in early education service delivery. It is also to encourage the implementation of inclusive education in early childhood education in early childhood services Inclusion every child deserves a good education services in accordance with the age and development, regardless of the degree, the economic conditions of disorder or mental, physical or social that is owned by a child. The most striking effect and can leave a long impression made at the right time, ie during the critical or sensitive period. Therefore, the need for stimulus is given at an early age can improve all aspects of the development is also based on that view. Delay or omission giving stimulus at the right time will be a negative impact on children's development.